An assessment of detection canine alerts using flowers that release methyl benzoate, the cocaine odorant, and an evaluation of their behavior in terms of the VOCs produced. (June 2015) - Cerreta, Michelle M.; Furton, Kenneth G.
Highlights: Results of this paper validate the reliability of canine evidence in court. The odor profiles of snapdragon flowers were found to be statistically different than cocaine. Methyl benzoate is not necessarily the dominant odor produced by snapdragon flowers. Narcotic detection canines never falsely alerted to snapdragon flowers. Abstract: In recent years, the high frequency of illicit substance abuse reported in the United States has made the development of efficient and rapid detection methods important. Biological detectors, such as canines ( Canis familiaris ), are valuable tools for rapid, on-site identification of illicit substances. However, research indicates that in many cases canines do not alert to the contraband, but rather to the volatile organic compounds (VOCs) that are released from the contraband, referred to as the "active odor." In 2013, canine accuracy and reliability were challenged in the Supreme Court case, State of Florida v. Jardines . In this case, it was stated that if a canine alerts to the active odor, and not the contraband, the canine's accuracy and selectivity could be questioned, since many of these compounds have been found in common household products. Specifically, methyl benzoate, the active odor of cocaine, has been found to be the most abundant compound produced by snapdragon flowers. Therefore, the purpose of this study is to evaluate the odor profiles of various species of snapdragon flowers to assess how significantly methyl benzoate contributes to the total VOC profile or fragrance that is produced. Particularly, this study examines the VOCs released from newly grown snapdragon flowers and determines its potential at eliciting a false alert from specially trained detection canines. The ability of detection canines to differentiate between cocaine and snapdragon flowers was determined in order to validate the field accuracy and discrimination power of these detectors. An optimized method using headspace solid-phase microextraction coupled with gas chromatography–mass spectrometry (HS–SPME/GC–MS) was used to test the different types and abundances of compounds generated from snapdragon flowers at various stages throughout the plants' life cycle. The results indicate that although methyl benzoate is present in the odor profile of snapdragon flowers, other compounds are present that contribute significantly, if not more, than that of methyl benzoate. Canine teams, from various police departments throughout South Florida, certified for narcotics detection, took part in this study. Two canine trials involving 21 canines teams were performed by exposing the teams to 4 different species of snapdragon flowers. Of the 21 canine teams tested, none alerted to the snapdragon flowers presented, while all (100%) alerted to real cocaine samples, the positive control. Notably, the results revealed that although methyl benzoate is produced by snapdragon flowers, certified narcotics detection canines can distinguish cocaine's odor profile from that of snapdragon flowers.